The theory of linear and nonlinear magnetoelectric effect in layered disc–shaped magnetostrictive-piezoelectric composites - T. A. Galichyan; D. A. Filippov; T. O. Firsova; G. S. Radchenko (National Academy of Sciences of Armenia)
The theory of linear and nonlinear magnetoelectric effect in layered magnetostrictive-piezoelectric multiferroics is presented based on the joint solution of the equations of motion and constitutive relations for the magnetostrictive and piezoelectric subsystems, considering the boundary conditions on the interface. It is shown that, in weak bias magnetic fields, the value of nonlinear effect is comparable with linear, and along with the main resonance, there is an additional resonance. Value of the resonance amplitude is not dependent on bias magnetic field and is excited at the frequency of magnetic field twice less the main resonance frequency. Trilayer nickel–polymer–PZT–polymer nickel disc-shaped structure is designed for the experiment. Frequency and field dependence of magnetoelectric effect is presented for this structure. В статье представлена теория линейного и нелинейного магнитоэлектрического эффекта в слоистых магнитострикционно-пьезоэлектрических мультиферроиках, построенная на основе решений материаль¬ных уравнений и уравнения движения среды для пьезоэлектрической и магнитострикционной подсистем по отдельности с учётом условий на границе раздела. Показано, что в слабых полях подмагничивания величина нелинейного эффекта сравнима с линейным, причём, наряду с основным резонансом, наблю¬да¬ется дополнительный резонанс. Величина амплитуды этого резонанса не зависит от поля подмагни¬чивания, а возбуждение происходит на частоте магнитного поля в два раза меньшей частоты основного резонанса. Հոդվածում նեկայացված է գծային և ոչ գծային մագնիսաէլեկտրական էֆեկտի տեսությունը մագնիսաստրիկցիոն-պյեզոէլեկտրական բազմաֆեռոիկներում: Տեսությունը կառուցված է նյութական հավասարումների, պյեզոէլեկտրական և մագնիսաստրիկցիոն միջավայրերի շարժման համապատասխան հավասարումների լուծման հիման վրա, հաշվի առնելով եզրային պայմանները: Ցույց է տրված, որ թույլ մագնիսականացնող դաշտերում ոչ գծային էֆեկտի մեծությունը համեմատական է գծային էֆեկտի մեծության հետ, ընդ որում հիմնական ռեզոնանսի հետ նկատվում է նաև լրացուցիչ ռեզոնանս: Այդ ռեզոնանսի ամպլիտուդի մեծությունը կախված չէ մագնիսականացնող դաշտից, իսկ գռգռումը տեղի է ունենում հիմնական ռեզոնանսի հաճախությունից երկու անգամ փոքր մագնիսական դաշտի հաճախության դեպքում:
Keywords: Mechanics of deformable solids; Coupling of solid mechanics with other effects